Pembelajaran Bahasa Inggris bagi Anak-anak Usia TK di Dusun Ngroto - Nathania Yunita Dharma; Manasye Dion Anugrah; Sonia Theodory Tenggawana; Maria Zella Pascal Rustam; Virginia Carztensa Pattipi; Alvianto Wahyudi Utomo (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
English is recognized as an international language with the largest number of speakers in the world. Currently, the ability to speak English is considered to be one of the skills that should be mastered by everyone, especially for children. According to developmental psychology, school-age children are generally in the critical period stage. At this stage, children are able to absorb the language to the maximum so that English language education for children at school age is felt to be more appropriate to do. Unfortunately, access to English language education in some places is very limited, including in Ngroto Village. The limited access to English education in Ngroto Village is caused by the limited number of available teachers. Therefore, this activity focuses on teaching English for school-age children, especially for kindergarten and elementary school age through English tutoring activities. This English tutoring activity is also part of Penelitian Lapangan Terpadu (PLT) Faculty of Social Science and Communication SWCU.